2017
DOI: 10.1002/bdr2.1178
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, cognition, and the adolescent brain

Abstract: Few adolescents engage in the recommended levels of physical activity, and daily exercise levels tend to drastically decrease throughout adolescence. Beyond physical health benefits, regular exercise may also have important implications for the teenage brain and cognitive and academic capabilities. The current paper reviews a number of studies showing that regular patterns of exercise and physical activity relate to academic performance, cognitive function, brain structure, and brain activity in adolescents. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 79 publications
2
54
1
Order By: Relevance
“…10 Exercise-induced activation of a growth protein known as brain-derived neurotrophic factor is thought to contribute, with the suggestion that aerobic fitness is linked to cortical brain development. 10 Cognitive benefits of exercise may be particularly relevant for children with brain tumors, who are at higher risk of inactivity 5 and of suffering long-term pulmonary and endocrine disorders. 3 Vigorous exercise in early adulthood is associated with a lower risk of cardiovascular events 4 and the risk of mortality 11 in adult survivors of childhood cancer, independent of treatment-related factors.…”
Section: General Benefits Of Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…10 Exercise-induced activation of a growth protein known as brain-derived neurotrophic factor is thought to contribute, with the suggestion that aerobic fitness is linked to cortical brain development. 10 Cognitive benefits of exercise may be particularly relevant for children with brain tumors, who are at higher risk of inactivity 5 and of suffering long-term pulmonary and endocrine disorders. 3 Vigorous exercise in early adulthood is associated with a lower risk of cardiovascular events 4 and the risk of mortality 11 in adult survivors of childhood cancer, independent of treatment-related factors.…”
Section: General Benefits Of Exercisementioning
confidence: 99%
“…Physical exercise is an underestimated tool for improving executive functioning in children cured of brain tumors, since cardiopulmonary fitness has been associated with improved cognitive outcomes in both adults and children . Exercise‐induced activation of a growth protein known as brain‐derived neurotrophic factor is thought to contribute, with the suggestion that aerobic fitness is linked to cortical brain development . Cognitive benefits of exercise may be particularly relevant for children with brain tumors, who are at higher risk of inactivity and of suffering long‐term pulmonary and endocrine disorders .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its health benefits, physical activity has a positive impact on cognition. [1] Several human and animal studies have revealed the neurobiological mechanisms underlying the impact of physical activity on cognition. [2] There has been a tremendous progress in the last decade about the molecular mechanisms, through which exercise improves mental health.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization has suggested the daily recommendation of 60 min of moderate-to-vigorous intensity physical activity for children and adolescents (5 to 17 years) population. [1] Regular or chronic exercise is a planned, structured and repetitive physical activity, which aims to improve and maintain physical fitness. Within the domain of physical activity, aerobic exercise seems to have more beneficial effects when compared to resistance exercises, though some of the studies have reported beneficial effects with both aerobic [3] and resistance exercises.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Apart from its health benefits, physical activity has a positive impact on cognition. [11] Several human and animal studies have revealed the neurobiological mechanisms underlying the impact of physical activity on cognition. [12] Studies have documented that aerobic exercise is associated with positive neurological and cognitive outcomes in children and older adults.…”
Section: Introductionmentioning
confidence: 99%